“He was on the Don and served in Siberia”: Ataman Dementy Zlobin and his Descendants in State Service in the 17th Century - Kamenetskii, Ivan P. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
In their study, the author examines the life and service activities of one of the most prominent Siberian atamans, former Don Cossack Dementy Zlobin. Based on the analysis of the documentary material, the author established Zlobin's origin, social and financial position, kinship, as well as his participation in the events of the Time of Troubles and service in Siberia. It is shown through an analysis of said material, that thanks to his military experience and leadership qualities acquired on the Don and in Central Russia during the Time of Troubles, D. Zlobin rose from an ordinary Cossack to an influential Siberian ataman. It is noted that D. Zlobin served in the difficult conditions of the South Siberia frontier, with under constant danger and threats from nomadic rulers, and other difficulties associated with the initial development of the southern part of the Yenisei region by the Russian Empire. During his service in the Krasnoyarsk prison, the ataman led many military campaigns against warlike nomads, actively defended the interests of the service class people before the military governors and central authorities and was engaged in economic activities. The author also considers the ataman’s family environment and the performance of official duties by his sons and grandsons. The author makes the conclusion about the typicality and significance of the figure of D. Zlobin and his descendants, who in many respects corresponded to the behavioral stereotypes of their social environment, a characteristic of the Russian oldtimer population of Siberia, and who have made significant contribution to its development.